CONVERGENCE OF ACCOUNTING STANDARDS: IMPLICATIONS TO THE NIGERIAN ECONOMY (Journal of Global Accounting, 2023)
The study sought to empirically determine the effect of the disclosures and presentation of accounting information in line with International Financial Reporting Standards on the Nigerian economy. It investigated whether IFRS adoption suits the Nigerian economy in terms of Foreign Direct Investment, and market capitalization. In order to capture the macro-economy as a whole, control variables were introduced into the models which were inflation, corruption, human capital development and monetary policy rate. The granger causality test and multiple regression analyses were used to analyse the data. The findings reveal that IFRS adoption had a significant positive effect on FDI. Market capitalization however, was not affected by IFRS adoption. The study concludes that IFRS adoption significantly affects the Nigerian economy though this effect is dependent on other economic factors as outlined in the control variables. It is therefore recommended that a hybrid form of accounting standard (IFRSs and SASs) is adopted to fit the Nigerian environment.
Keywords: International Financial Reporting Standards [IFRS]; Foreign Direct Investment [FDI]; Market Capitalisation